Melt structure and dynamics of unentangled polyethylene rings: Rouse theory, atomistic molecular dynamics simulation, and comparison with the linear analogues - Tsolou, Georgia; Stratikis, Nikos; Baig, Chunggi; Stephanou, Pavlos S.; Mavrantzas, Vlasis G. (My University, 2010)
Atomistic configurations of model unentangled ring polyethylene (PE) melts ranging in chain length from C24 up to C400 have been subjected to detailed molecular dynamics (MD) simulations in the isothermal-isobaric statistical ensemble at temperature T = 450 K and P = 1 atm. Strictly monodisperse samples were employed in all cases. We present and discuss in detail simulation results for a variety of structural, thermodynamic, conformational and dynamic properties of these systems, and their variation with chain length. Among others, these include the mean chain radius of gyration, the pair correlation function, the intrinsic molecular shape, the local dynamics, the segmental mean square displacement (msd), the chain center-of-mass self-diffusion coefficient DG, the chain terminal relaxation time τd, the characteristic spectrum of the Rouse relaxation times τp, and the dynamic structure factor S(q,t). In all cases, the results are compared against the corresponding data from simulations with linear PE melts of the same chain length (the linear analogues) and the predictions of the Rouse theory for polymer rings which we derive here in its entirety. The Rouse theory is found to provide a satisfactory description of the simulation findings, especially for rings with chain length between C50 and C170. An important finding of our work (from the observed dependence of DG, τp, ζ, and η0 on chain length N) is that PE ring melts follow approximately Rouse-like dynamics even when their chain length is as long as C400; this is more than twice the characteristic crossover chain length (∼C 156) marking the passage from Rouse to reptation dynamics for the corresponding linear PE melts. In a second step, and by mapping the simulation data onto the Rouse model, we have managed to extract the friction coefficient ζ and the zero-shear rate viscosity η0 of the simulated ring melts. Overall, and in agreement with previous theoretical and experimental studies, our simulation results support that the structure of ring polymers in the melt is more compact than that of their linear analogues due to their nonconcatenated configurations. Additional results for the intermolecular mer-mer and center-of-mass pair correlation functions confirm that the effective correlation hole effect is more pronounced in melts of rings than in melts of linear chains. © 2010 American Chemical Society.
Keywords: Polymers; Rings (components); Cyclic polymer